1979
DOI: 10.1177/002221947901200614
|View full text |Cite
|
Sign up to set email alerts
|

Using the Neurological Impress Method with Learning Disabled Readers

Abstract: T he Neurological Impress Method (NIM) attempts to teach reading skills by having the pupil and the teacher read aloud in unison. The method is described in precise detail by Heckelman (1969). However, little research has been conducted regarding the NIM, and none has been published relating the NIM to learning disabled pupils.Gardner (1965), Embrey (1968), Heckleman (1969), and Langford, Slade, and Barnett (1974) have reported success with various adaptations of the NIM. However, because of the absence of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…It replicated much of the previous research with assisted reading (Alber-Morgan et al, 2007;Gilbert et al, 1996;Sherman et al, 2009;Van Holmes & McLaughlin, 1987;Van Wagenen et al, 1987) and its many variations (Blum & Koskinen, 1991;Carbo, 1970;Cunningham, 1978, Heckelman, 1979Lorenz, 1979;Samuels, 1979). In the present analysis, we could employ assisted reading in a unique classroom setting in a hospital.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It replicated much of the previous research with assisted reading (Alber-Morgan et al, 2007;Gilbert et al, 1996;Sherman et al, 2009;Van Holmes & McLaughlin, 1987;Van Wagenen et al, 1987) and its many variations (Blum & Koskinen, 1991;Carbo, 1970;Cunningham, 1978, Heckelman, 1979Lorenz, 1979;Samuels, 1979). In the present analysis, we could employ assisted reading in a unique classroom setting in a hospital.…”
Section: Discussionsupporting
confidence: 75%
“…The student is required to follow the teacher's finger and read along with the teacher. Although Lorenz (1979) suggested that this procedure might hold promise for students with learning disabilities, he cautioned that the impress method would most likely be less effective with children who have auditory learning disabilities because of the method's dependence on the auditory modality.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this strategy is to increase fluency by having students and teachers read aloud simultaneously. Although preliminary findings for the method were encouraging, subsequent studies did not produce significant results (Langford et al, 1974;Lorenz & Vockell, 1979).…”
Section: Methodsmentioning
confidence: 95%
“…Fluency strategies have been designed and empirically tested. One of the first empirically evaluated strategies to focus on fluency was the neurological impress method (Hollingsworth, 1970(Hollingsworth, , 1978Langford, Slade, & Barnett, 1974;Lorenz & Vockell, 1979). The goal of this strategy is to increase fluency by having students and teachers read aloud simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Anecdotal evidence suggested that the students developed more positive attitudes toward reading, were more motivated to pick up a book voluntarily and read it, and appeared more confident in their ability to read (Lorenz & Vockell 1979). Conversely, research also has shown that the method failed to produce gains in reading fluency (Hollingsworth 1970), word recognition, and comprehension (Lorenz & Vockell 1979). The contradictory research findings concerning the NIM leave the practitioner without a clear empirical basis from which to evaluate the applicability of the NIM for classroom instruction, and particularly for learning disabled children.…”
mentioning
confidence: 99%